Lauric Acid Is a Potent Biological Control Agent That Damages the Cell Membrane of Phytophthora sojae - Liang, Changhui; Gao, Wenteng; Ge, Ting; Tan, Xinwei; Wang, Jiayu; Liu, Huaxin; Wang, Yong; Han, Chao; Xu, Qian; Wang, Qunqing (Frontiers in Microbiology, 2021)
Sustainable management of plant pathogens becomes more challenging, and novel solutions are needed. Biologically active secondary metabolites in plants are important source of novel crop protection chemistry. The individual effective compounds of these natural products have the potential to be success new agrochemicals. Lauric acid was identified from defense soybean leaf volatile, and inhibit the growth of Phytophthora sojae, the causal agent of soybean root rot. Lauric acid could influenced the mycelia development, sporangium formation, zoospores generation and germination by destroying the P. sojae cell membrane. Lauric acid derivatives, such as monolaurin, also have the similar biologically active. Both lauric acid and monolaurin are safe to soybean plants under 0.3 g a.i./plant, and can promote the soybean growth, imply the potential to be an eco-friendly biological control agent.